The Influence of The Principals' Leadership Style in Islamic Education Management on Teachers' Work Motivation and Performances - Akhyar, Yundri (Mudir : Jurnal Manajemen Pendidikan, 2023)
Teachers and staff have become less motivated to do their jobs and produce poor results because of the principals' lack of progressive leadership. The purpose of this research is to identify how a principal's leadership style affects employee morale and classroom outcomes. This study is an example of research done after the fact. Twenty-one educators from MAS Al-Kifayah Riau made up the sample for this research. This sample was collected using a method known as total sampling, in which the sample size is equal to the population size. This study employs a non-test approach to data collection. Distributed questionnaires gathered information on principal leadership styles, teacher work motivation, and document recording gathered information on teacher performance. The product-moment correlation analysis can be used to test hypotheses. The results showed that while there was a correlation between the principal's leadership style and teachers' output, there was no such link between the principal's style and teachers' drive to succeed in the classroom.